What are the prevailing infrastructure funding models in SubSaharan Africa? - Seroke, Setumo (My University, 2016)
This paper assesses and describes the various prevailing infrastructure financing mechanisms in Sub-Saharan Africa (SSA). This study, through a multi-country regression panel framework of the top 10 recipients of Public Private Partnerships (PPP) investments in Sub-Saharan African between 1991 and 2014, finds that government budget constraints, macroeconomic conditions and institutional quality are significant determinants of infrastructure finance. Policy implications are that SSA governments need to focus on building and maintaining sound fiscal and monetary discipline. Institutional factors cannot be ignored in this process, as these are critical to creating an environment that is conducive to building trust and reducing risk perceptions for potential investors as well as providing the room for innovative solutions.
Research thesis submitted in fulfilment of the requirements for the degree of Masters of Management in Finance & Investment